The Islamization of the Social Sciences: A Review - Awaru, A. Octamaya Tenri; Salam, Rudi; Torro, Supriadi; Suhaeb, Firdaus W. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The Islamization of Social Sciences (IOSS) intends to comprehend Islam within the context of the contemporary world. This is aimed So that Muslims would be able to carry their political, social and economic affairs in consonance with the injunctions of Islam and in relevance to the modern exigencies to ensure a socially healthy, politically cohesive to face the challenges of the 21st century. Steeped into their own tradition, the Muslim scholars working for the project ably try to apply the systematic and scientific approach in every field of Social Sciences and provided Islamic intellectual thought and knowledge in such fields. The present work tries to provide a comprehensive survey of the writings on IOK since its inception in the 1980s with special emphasis on the writings on Islamization of Social Sciences (IOSS) and providing a breakdown of categories of writings available on this subject. The objective of the study is to analyze the works and researches carried out in the field of Islamization of knowledge especially in the field of Social Sciences. The study aims to find the success and failure of the project.